Plumbers and pipe fitters library : installation, heating, and welding - Oravetz, Jules Sr. (Indianapolis : Theodore Audel, 1967)
This book have been written to aid those who are active in these trade and to aid those who desire to become plumbers and pipe fitters
Includes index
ijb 16/01/2019
Loans
Keywords: Fixtures and fittings; Pipe fitting; Plumbing; Water-supply; Building